Assessment of Edupreneurship Skills Acquisition among Pre-Service English Language Teachers in the 21st Century in Adeyemi Federal University of Education, Ondo - OLUDARE, Bosede Abiola (Ilorin Journal of Education, 2025)
This study assesses edupreneurship skills acquisition among pre-service English language teachers in the 21st century in Adeyemi Federal University of Education, Ondo. The objective of this study is to evaluate the effectiveness of the current practical training curriculum in equipping pre-service English language teachers with the necessary skills to initiate and manage entrepreneurial ventures. A descriptive survey research design was adopted for the study. The population of the study consists of all English pre-service of the University, Ondo, 25 respondents each were randomly selected across 100 to 400 levels in the department. Three research questions and one hypothesis were answered. The was validated by an expert in test and measurement and the reliability measure used in getting its reliability was Cronbach alpha which yielded reliability index 0.72. The collected data were analyzed using simple percentage, mean scores, standard deviation and t-test statistical methods. The findings indicated that pre-service English language teachers were introduced to entrepreneurship courses and handwork skills of their choice during the first semester of their academic program. However, it was found that the current practical training curriculum does not adequately equip them with the necessary skills to initiate and manage entrepreneurial ventures in education. The study concluded that while entrepreneurship courses and handwork skills acquisition have positively impacted pre-service teachers’ perception of edupreneurship, they have also boosted their confidence in pursuing education-related business ventures. It was recommended that tertiary institutions should foster edupreneurship professional development for teachers through partnerships with entrepreneurial organizations, and mentorship programs.